Translating the English Bible from relevance to deconstruction - Goodwin, Philip W. (Cambridge James Clarke, 2013)
Front cover -- Dedication -- Title page -- Contents -- Figures and Tables -- Preface -- Note to the reader -- Abbreviations -- Chapter One: The Holy Marriage -- David Daniell and the lost art of translation -- The rules of the art -- The problem of fidelity -- The curse of the Holy Marriage -- The need for theory -- What kind of theory? -- Chapter Two: Challenging the Holy Marriage:Relevance Theory and translation -- What is Relevance Theory? -- Interpretive resemblance -- Relevance Theory of Translation (RTT) -- Why Relevance Theory? -- How RTT will be used in the present work -- Chapter Three: Start as you mean to go on? Syntax in Luke 1.1-4 -- The source text: relevance in its context? -- Contextual implications from Luke's preface -- Translating Luke's preface -- Towards a relevant translation? -- Chapter Four: When is a priest not a priest? -- The case of a certain priest -- Achieving relevance in context -- In translation -- Challenging the consensus -- The persistence of the tradition -- Alternative translations -- Chapter Five: Still looking for clues -- Clues arising from syntactic properties -- Clues arising from phonetic properties -- Clues arising from semantic constraints on relevance -- Clues arising from formulaic expressions -- Clues arising from onomatopoeia -- Clues arising from the stylistic value of words -- Clues from sound-based poetic qualities -- Are there other clues? -- Uses and abuses of communicative clues -- Chapter Six: Repetitive texture and four kinds of literalism -- Repetitive texture -- Repetitive texture in translation -- Concordance: a non-topic? -- Concordance and literalism -- Four motivations for literalism -- The perfect translation -- Final remarks: The experimental translation -- Appendix - Experimental Translation of Luke 1-2 -- Bibliography -- Back cover.
""Four motivations for literalism""""The perfect translation""; ""Final remarks: The experimental translation""; ""Appendix - Experimental Translation of Luke 1â€?2 ""; ""Bibliography""; ""Back cover ""
Includes bibliographical references and index -- Includes bibliographical references
Keywords: Bible -- Versions; Bible -- Translating; Equivalence (Linguistics); Bible ; Translating ; History; Electronic books